1987
DOI: 10.1161/01.cir.75.3.533
|View full text |Cite
|
Sign up to set email alerts
|

Coronary hemodynamics and myocardial metabolism of lactate, free fatty acids, glucose, and ketones in patients with septic shock.

Abstract: To investigate disturbances in the coronary circulation and myocardial metabolism during septic shock, we examined coronary sinus blood flow and myocardial substrate extraction in 40 patients with septic shock and 13 control patients. Patients with coronary artery disease were excluded from this study. The global hemodynamic pattern of the septic patients was characterized by a lower stroke volume, despite an elevated cardiac index. Coronary sinus blood flow was high (187 + 47 vs 130 ± 21 ml/min in the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
125
1
12

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(146 citation statements)
references
References 34 publications
8
125
1
12
Order By: Relevance
“…The only exception, however, is lactate, the uptake of which is 15 times higher than in control lambs. This is the result not only of an increased myocardial blood flow but also of an additionally increased lactate An increased myocardial lactate utilization has been previously demonstrated at rest (35,36), during exercise (4, 10-12, 17, 35, 37-39), or during septic shock (40). However, a common feature in all of these studies is an increased arterial lactate concentration.…”
Section: Discussionmentioning
confidence: 78%
“…The only exception, however, is lactate, the uptake of which is 15 times higher than in control lambs. This is the result not only of an increased myocardial blood flow but also of an additionally increased lactate An increased myocardial lactate utilization has been previously demonstrated at rest (35,36), during exercise (4, 10-12, 17, 35, 37-39), or during septic shock (40). However, a common feature in all of these studies is an increased arterial lactate concentration.…”
Section: Discussionmentioning
confidence: 78%
“…In a recent human autopsy study of patients who had succumbed to severe sepsis, buildup of lipids was found inside cardiomyocytes (51). During sepsis, human cardiomyocytes have also displayed diminished uptake of ketone bodies, free fatty acids, and glucose (23). In parallel, septic mice presented with increased intracardiomyocyte deposits of glycogen (52).…”
Section: Metabolic Changesmentioning
confidence: 98%
“…This hypothesis was soon abandoned after direct measurements of coronary blood flow were obtained, showing no reduced, but rather increased, coronary blood flow (22,23). In later studies, however, increased levels of plasma troponin were observed and correlated with the severity of myocardial depression during sepsis and septic shock (24).…”
Section: Decreased Coronary Blood Flowmentioning
confidence: 99%
“…Myocardial depression and elevated serum levels of cardiac troponin are common in sepsis, and associated with poor outcome 6, 7. These findings are difficult to reconcile with the normal or even elevated myocardial blood flow found in sepsis 8, 9. Brain function is often affected very early in sepsis, so‐called septic encephalopathy, and survivors often show ischemic lesions on magnetic resonance imaging (MRI), suffering severe permanent neurological sequelae 10.…”
mentioning
confidence: 99%